Glycosylated hemoglobin as a forecast factor of progressing of diabetic nephropathy in patients with diabetes type 1. - Pertseva, N. O.; Chub, D. I. (Medicni Perspektivi, 2017)
The aim of the study was to propose a mathematical model for prediction of development of diabetic nephropathy in patients with diabetes mellitus by determining the level of glycosylated hemoglobin - as a factor in the development and progression of diabetic nephropathy. A survey of 136 patients with type 1 diabetes was performed in the endocrinology department of the OSH «Clinic of the Medical Academy», Dnipro in 2016-2017. Clinical laboratory examination included: determination of the level of glycosylated hemoglobin (HbA1c), level of blood creatinine, level of albuminuria. The GFR was calculated by the formula CKD-EPI.The obtained results of the study, using methods of correlation and regression analysis, show a clear correlation between the GFR score in patients with diabetes mellitus and the level of glycosylated hemoglobin. Statistical methods of analysis have shown that the level of glycosylated hemoglobin can be considered as an early predictor of development of diabetic nephropathy. The mathematical equation of prognosis for the onset of diabetic nephropathy can be used to determine the prognosis for the development of diabetic nephropathy in diabetes mellitus patients in clinical practice for the timely inclusion of patients with a high prognostic risk in a group requiring more stringent glycemic control.